Influence of clinical presentation, site, and extent of venous thrombosis on decision about duration of anticoagulation: Data from the international, prospective, observational WHITE study. Issue 211 (March 2022) - Palareti, Gualtiero; Bignamini, Angelo A.; Urbanek, Tomasz; Cini, Michela; Li, Young-Jun; Madaric, Juraj; Bouslama, Kamel; Sokurenko, German Y.; Andreozzi, Giuseppe M.; Matuška, Jiří; Mansilha, Armando; Barinov, Victor; et al.
Abstract: Background: Low attention has generally been dedicated to the influence of clinical presentation, extent of venous thrombosis and presence of residual vein obstruction (RVO) on the decision about the duration of secondary prophylaxis after a first venous thromboembolism (VTE). Aim: This study aimed at investigating the role of the mentioned VTE characteristics on the therapeutic decision using the information collected in the international, prospective, observational WHITE study. Results: 1240 patients were recruited by 79 clinical centers in 7 countries (China, Czechia, Poland, Portugal, Russia, Slovakia, and Tunisia). 35 patients had as index event a pulmonary embolism (PE) without a deep vein thrombosis (DVT), and all continued anticoagulation. We focused on the 1205 subjects with DVT. The treatment decision differed among countries; altogether, more than 85% of patients with proximal (with or without distal) DVT continued a prophylactic treatment with anticoagulants, or antithrombotics; 34% of patients with isolated distal DVT stopped treatment, and more than 85% of patients with a PE associated to a DVT continued treatment. At multivariable analysis, the presence of proximal DVT, signs of post-thrombotic syndrome (PTS), residual vein obstruction (RVO), maintenance <180 days and concomitant diseases was associated with increased probability to continue secondary prophylaxis. Conclusion: The presentation as proximal DVT (with or without PE) or isolated PE influenced the treating physicians' decision in favor of extension of secondary prophylaxis, together with the presence of concomitant diseases and local conditions which may increase the risk of post-thrombotic syndrome. Highlights: Optimal duration of treatment after venous thromboembolism remains uncertain. The role of the nature (unprovoked or provoked) of the events is still debated. We assessed the physicians' decision in seven countries with important differences. Secondary prophylaxis was preferred in cases guessed at high risk for recurrences. Higher risk was attributed to proximal DVT, residual thrombi, concomitant diseases.